Analysis of PTH serum concentration from internal jugular veins of patients with primary hyperparathyroidism - Davi Knoll Ribeiro; Murilo Catafesta das Neves; Rodrigo de Oliveira Santos; Marcio Abrahao (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: To evaluate whether the values of Parathyroid Hormone (PTH) collected from the internal jugular veins of patients with primary hyperparathyroidism can assist in the surgical approach. Methods: Prospective study of patients who underwent parathyroid adenoma excision by PHPT, collected right and left internal jugular vein blood sample for analysis of Parathyroid Hormone. Results: Twenty-nine patients underwent surgery. All patients had a decrease in peripheral PTH greater than 50% with a mean of 73.47%. PTH collection from the internal jugular veins was positive regarding the confirmation of parathyroid adenoma laterality in 22 cases (75.86%) and failure in 7 cases (24.14%), (p-value = 0.001). Comparing the success rates of the Methoxyisobutylisonitrile parathyroid scintigraphy (MIBI) tests, parathyroid Ultrasonography (USG) and PTH of internal jugulars in relation to location of adenoma laterality, we observed MIBI as localizer in 89.65% of the cases followed by the Jugular PTH with 75.86% and USG with 44.82%. Conclusion: PTH collection from the internal jugular veins is useful in patients with primary hyperparathyroidism who underwent surgery as a possible method of localization exams, indicating adenoma laterality. Leve of Evidence: Level III.